2015
DOI: 10.3906/bot-1404-20
|View full text |Cite
|
Sign up to set email alerts
|

The modified qualities of basil plants by selenium and/or ascorbic acid

Abstract: IntroductionAscorbic acid (AsA) is one of the most critical low molecular weight antioxidants and has control over crucial processes, including the cell cycle and cell wall expansion (Noctor and Foyer, 1998). Ascorbic acid, a water soluble compound, is known as a major redox buffer, one of the most abundant antioxidants, and a required cofactor for several enzymes. Its multiple implications in various critical aspects of key physiological processes like cell division, growth, signal transduction, photosynthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 41 publications
4
30
1
Order By: Relevance
“…In higher plants, although selenium has not yet been classified as an essential element, its role has been considered to be beneficial under stress (Terry et al, ). Our observations of Se enhanced TPC content in wheatgrass is also supported by (Oraghi Ardebili, Oraghi Ardebili, Jalili, & Safiallah, ) on basil plant ( Ocimum basilicum ) where exogenously applied Se significantly stimulated the enzyme phenylalanine ammonia lyase activity and thus increased soluble phenol content as compared with control. Table clearly indicated that, Se and UV‐B showed synergistic effect with total phenolic content increasing significantly w.r.t.…”
Section: Resultssupporting
confidence: 86%
“…In higher plants, although selenium has not yet been classified as an essential element, its role has been considered to be beneficial under stress (Terry et al, ). Our observations of Se enhanced TPC content in wheatgrass is also supported by (Oraghi Ardebili, Oraghi Ardebili, Jalili, & Safiallah, ) on basil plant ( Ocimum basilicum ) where exogenously applied Se significantly stimulated the enzyme phenylalanine ammonia lyase activity and thus increased soluble phenol content as compared with control. Table clearly indicated that, Se and UV‐B showed synergistic effect with total phenolic content increasing significantly w.r.t.…”
Section: Resultssupporting
confidence: 86%
“…The modifications in the photosynthetic pigments found in the nSe and/or NO-treated plants could be caused by the possible changes in the nutrition process, redistribution of minerals, and/or the status of antioxidant system. Se-provoked alterations in the different photosynthesis-related characteristics have been reported in the various plant species, like potato (Germ et al, 2007) and basil (Ardebili et al, 2015). Se toxicity have been attributed to its similarity to sulfur (S), thereby producing nonfunctional proteins and enzymes (Pilon-Smits and Quinn, 2010;Lindblom et al, 2013).…”
Section: Figurementioning
confidence: 99%
“…The dramatic increase in the proline content as a multifunctional cytoprotective agent may result from the nSe and/or NO applications. The Semediated modification in the amino acid metabolism has been introduced as a critical mechanism by which it may enhance plant resistance to stress condition (Ježek et al, 2011;Ardebili et al, 2015). Moreover, the modification in the nitrogen assimilation and metabolism may be considered as an alternative way to dissipate the excess energy, thereby reducing photoinhibition process and improving cellular protection.…”
Section: Nitrate Reductase and Prolinementioning
confidence: 99%
See 2 more Smart Citations